Pengaruh Sikap Dan Efikasi Diri Terhadap Minat Berwirausaha Pada Mahasiswa - Rico Septia B. (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Interest in entrepreneurship among students is still low, because many still have the mindset of being job seekers rather than opening jobs. Every individual has an interest in entrepreneurship based on different causes. This research aims to analyze how attitudes and self-efficacy influence students' interest in entrepreneurship. This research method uses a quantitative approach using multiple linear regression analysis. The population was taken from students of the retail management undergraduate study program at University The results of this research show that the coefficient of determination is 0.645 or equal to 64.5%, meaning that the attitude variable (X1) and self-efficacy variable (X2) simultaneously influence the entrepreneurial interest variable (Y) by 64.5%. Apart from that, the attitude variable (X1) and self-efficacy variable (X2) also partially have a positive effect on interest in entrepreneurship (Y).